Titanium/nanodiamond nanocomposites: Effect of nanodiamond on microstructure and mechanical properties of titanium. (5th October 2017) - Zhang, Faming; Liu, Suli; Zhao, Peipei; Liu, Tengfei; Sun, Jing
Abstract: Titanium (Ti)/nanodiamond (ND) nanocomposites with potential for biomedical applications were prepared by using spark plasma sintering technique. By means of X-ray diffraction, scanning electron microscopy, transmission electron microscopy and mechanical analysis, the Ti/ND nanocomposites were investigated, and thus the effect of ND on the microstructural and mechanical properties of Ti matrix was demonstrated. Experimental results showed that the Ti/ND nanocomposites exhibited pure α-Ti phase with ND concentrations from 0.1 to 0.35 wt% and with in-situ formed nano-TiC phase in 0.5–2.0 wt% NDs. The nanoindentation hardness, Young's modulus and compressive yield strength of the Ti/ND nanocomposites were significantly improved, as ND was incorporated into the Ti matrix. Improvements of hardness (60.2%), Young's modulus (27.4%) and compressive yield strength (24%) were achieved by doping of 0.5 wt% NDs in the Ti matrix but at an expense of ductility. The Ti/0.35 wt% NDs nanocomposites have the best integrated mechanical properties. These improvements could be ascribed to the outstanding mechanical properties of ND, homogeneous dispersion of ND nanoclusters, Orowan strengthening with ND/nano-TiC and carbon atom solid solution strengthening in the Ti/ND nanocomposites. Graphical abstract: Highlights: Titanium (Ti)/nanodiamond (ND) nanocomposites were successfully produced by SPS. Hardness and compressive yield strength of the nanocomposites are significantly improved but at an expense of ductility. The Ti/0.35wt%ND nanocomposites have the best integrated mechanical properties. Orowan strengthening and C atom solid solution strengthening are the main strengthening mechanisms.